PENGARUH KUALITAS LAYANAN DAN DIVERSIFIKASI BISNIS TERHADAP KEPUASAN PELANGGAN MELALUI PENGALAMAN PELANGGAN DENGAN TRUST SEBAGAI MODERASI PADA SPBU - Sitorus, Victor Dean Rizky Maulana; Susilawati, Wati; Alamanda, Dini Turipanam (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of service quality and business diversification on customer satisfaction through customer experience, with trust as a moderating variable at gas stations (SPBU) operated by PT Pangandaran Putra. A quantitative approach was employed using a survey method involving 150 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that service quality and business diversification have a positive and significant effect on customer satisfaction, both directly and indirectly through customer experience. Customer experience is proven to act as a significant mediating variable, while trust has a positive effect on customer satisfaction but shows a negative moderating effect on the relationship between customer experience and satisfaction. These findings highlight that customer satisfaction is not only determined by service quality and business diversification but also by customer experience as a key mechanism, supported by customer trust.